Revealing How Coca Cola Successfully Broke into Indonesia Market with a Coke - Donny Susilo (Entrepreneurship Faculty, Universitas Garut, 2021)
Indonesia has been attractive investment destination to many multinational companies since a long time ago, due to its big population, plenty natural resources and cheap labors, including to Coca Cola. This study aims to analyze international market entry and business strategy of Coca Cola when entering Indonesia market. Moreover, this study also aims to identify internal and external factor that affects Coca Cola business in Indonesia by SWOT analysis, resulting in growth strategy recommendation. The result reveals out that Coca Cola came to Indonesia by foreign direct investment at first time, but then decided to expand their distribution all over Indonesia. Therefore, they opened opportunity for franchise. By keeping their secret formula, they can provide differentiation that makes them remains competitive. The strategy adopted by Coca Cola Amatil Indonesia to conquer Indonesia market is transnational strategy, which has characteristics of high in local responsiveness and also high in global integration. Meanwhile, the SWOT analysis suggests that Coca Cola should put priority on market penetration first instead of market development for the time being. Company should focus on sales and distribution in specific market first then explore more market for their product. There are still many possible markets to exploit in Indonesia as well as abroad.